2018
DOI: 10.1038/s41467-018-06244-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials design for super-degenerate electronic state beyond the limit of geometrical symmetry

Abstract: Spherical atoms have the highest geometrical symmetry. Due to this symmetry, atomic orbitals are highly degenerate, leading to closed-shell stability and magnetism. No substances with greater degrees of degeneracy are known, due to geometrical limitations. We now propose that realistic magnesium, zinc, and cadmium clusters having a specific tetrahedral framework possess anomalous higher-fold degeneracies than spherical symmetry. Combining density functional theory calculations with simple tight-binding models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It was confirmed that all the obtained structures have no imaginary frequencies. A small part of the present clusters has also been discussed in our recent paper 41 , including Mg 4 , Mg 10 , Mg 20 , Zn 4 , Zn 10 , Zn 20 , Cd 4 , Cd 10 , Cd 20 , Si 10 , Ge 10 , Sn 10 , Pb 10 , Al 6 Sn 4 , Ga 6 Sn 4 , and In 6 Sn 4 .…”
Section: Methodssupporting
confidence: 58%
“…It was confirmed that all the obtained structures have no imaginary frequencies. A small part of the present clusters has also been discussed in our recent paper 41 , including Mg 4 , Mg 10 , Mg 20 , Zn 4 , Zn 10 , Zn 20 , Cd 4 , Cd 10 , Cd 20 , Si 10 , Ge 10 , Sn 10 , Pb 10 , Al 6 Sn 4 , Ga 6 Sn 4 , and In 6 Sn 4 .…”
Section: Methodssupporting
confidence: 58%
“…This tendency is rationalized by the thermodynamic stability based on the electronic configurations unique to clusters typified by superatoms. [6][7][8]25,32,36,47,90 These clusters generally have relatively rigid structures with large bond angles of up to 90°originating from p-electrons and the ability to contain a few atoms of other group elements in electronically stabilized skeletons. In particular, the endohedral structures typified by stannaspherenes mentioned in the gas-phase synthesis section enable the incorporation of other groups of elements without ligands.…”
Section: Naked Elementary Clustersmentioning
confidence: 99%
“…[1][2][3] On the other hand, their electronic states of clusters resemble more closely those of molecules than bulk materials (including nanoparticles), leading to their unique characteristics. [4][5][6][7][8] Such clusters contribute to the manifestation of highly efficient and sophisticated biological functions in nature, such as water oxidation in photosynthesis, electron transfer, nitrogen fixation, and breathing. [9][10][11][12][13] Moreover, clusters possess various structural characteristics that are not observed in other chemicals, including the number of constituent atoms, types of constituent elements, elemental ratios, atomic arrangements, and geometrical symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Particularly, atomic clusters, which are ultrasmall substances up to sub-nanosize scale ( � 1 nm), have attracted attention because they possess unusual properties not found in general NPs. [6][7][8][9][10][11] In contrast to NPs whose properties are dependent on particle size, [4,12] sub-nanoparticles (SNPs), including the clusters, can also be regarded as inorganic molecules because their properties are determined by quantum chemical factors such as molecular orbitals and structural symmetry [11,[13][14][15] and differ dramatically depending on the number of constitutive atoms. [16][17][18] Although the origins of the properties of NPs (> 3 nm) and SNPs ( � 1 nm) are different, their border, which exists in the quasi-sub-nano region (1-3 nm, 60-1000 constitutive atoms), [18] has not been clarified.…”
mentioning
confidence: 99%